Ethno-Entomophagy (Valanga nigricornis): Societal Perspectives, Natural Pest Control and Environmental Sustainability - Astuti, Dwi Setyo; Sajidan, S; Suciati, S; Masykuri, Mohammad (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
The practice of ethno-entomophagy has been going on for hundreds of years in Indonesia and has become a local culture and wisdom that still continues today. Of the many edible insects, Valanga nigricornis is one of the most popular. The aim of this research is to determine the views of local communities towards entomophagy and its impact on natural pest control and environmental sustainability. The method used is phenomenological research using snowball sampling techniques and quantitative descriptive research using purposive sampling techniques. The research area is 4 hectares of rice fields. Sampling was carried out in 5 plots with an area of 300 m2 each and was carried out once a year continuously for 3 years. The sampling time was chosen at the beginning of the dry season which is the peak time for corn production. The research results show that the main reasons and beliefs of local people towards the practice of entomophagy are caused by cultural factors, natural pest control, economic factors, and favorite foods. The results of sampling regarding Valanga nigricornis pest attacks showed low values for 3 consecutive years. The conclusion of this research is that ethno-entomophagy has a positive impact on local control of the natural pest Valanga nigricornis.